2010
DOI: 10.2217/imt.10.10
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response Against Tumor Antigens Expressed on Human Cancer Stem-Like Cells/Tumor-Initiating Cells

Abstract: Cancer stem-like cells (CSCs)/tumor-initiating cells (TICs) are a small population of cancer cells that have the properties of tumor-initiating ability, self-renewal and differentiation. These properties suggest that CSCs/TICs are essential for tumor maintenance, recurrence and distant metastasis. Thus, elimination of CSCs/TICs is essential to cure malignant diseases. However, there are several studies reporting that CSCs/TICs are more resistant to standard cancer therapies, including chemotherapy and radiothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 62 publications
1
45
0
Order By: Relevance
“…15 We previously demonstrated that SOX2-overexpressing lung adenocarcinoma cell lines showed higher rates of side population cells and higher tumorigenecity and that SOX2 mRNA knockdown of side population cells by gene-specific siRNA completely abrogated tumorigenecity in vivo. 33 In this study, we found that SOX2 was associated with cancer-specific survival in patients with upper urinary tract urothelial cell carcinoma.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…15 We previously demonstrated that SOX2-overexpressing lung adenocarcinoma cell lines showed higher rates of side population cells and higher tumorigenecity and that SOX2 mRNA knockdown of side population cells by gene-specific siRNA completely abrogated tumorigenecity in vivo. 33 In this study, we found that SOX2 was associated with cancer-specific survival in patients with upper urinary tract urothelial cell carcinoma.…”
Section: Discussionmentioning
confidence: 95%
“…1 Cancer stem-like cells/tumor-initiating cells are a small population of cancer cells that have the properties of tumor-initiating ability, self-renewal and differentiation. Cancer stem-like cells/tumor-initiating cells are more resistant to chemotherapy and radio-therapy than non-cancer stem-like cell/tumor-initiating cell populations via various mechanisms, 15 suggesting that the existence of these cells is a prognostic factor in cancer patients. In this study, we investigated two cancer stem-like cell/tumor-initiating cell markers.…”
mentioning
confidence: 99%
“…Thus, therapy targeting the small population of CSCs/ CICs might be a reasonable approach for treatment of resistant and advanced cancers. Some immunologic effector cells, including natural killer (NK) cells and gdT cells, have been reported to be able to efficiently recognize the CSC/CIC population (14). Furthermore, we have reported that CTLs can efficiently recognize human colon CSCs/CICs (16).…”
Section: Introductionmentioning
confidence: 93%
“…In advanced cases, however, complete Cancer cells in solid carcinomas display heterogeneity in many aspects of their phenotypes, and only a small population of cells, called cancer stem-like cells/cancer-initiating cells (CSC/CIC), express stem cell phenotype and have high tumorinitiating ability (cancer stem cell hypothesis; refs. [12][13][14]. CSCs/CICs are resistant to chemotherapy and radiotherapy by various mechanisms, and these characteristics of CSCs/ CICs are thought to be related to posttherapeutic recurrence (15).…”
Section: Introductionmentioning
confidence: 99%
“…3 At this time, there are no definitive markers of CSCs/CICs; however, three major methods for enriching CSC/CIC population have been described. 4 One is side population (SP) cells based on the efflux of Hoechst 33342 dye. 5 CSCs/CICs were successfully isolated as SP cells in several types of cancers.…”
mentioning
confidence: 99%